Enhancement of thermal conductivity and kinematic viscosity in magnetically controllable maghemite (γ-Fe2O3) nanofluids - Nurdin, Irwan; Yaacob, Iskandar Idris; Johan, Mohd. Rafie (ELSEVIER SCIENCE INC, 2016)
The objective of this study is to investigate the thermal conductivity and kinematic viscosity enhancement of maghemite nanofluids at various particle volume fractions (0.1%, 0.2%, 0.3%, 0.4%, 0.5% and 0.6%) under the influence of an external magnetic field in different orientations (parallel and perpendicular). The effect of magnetic field strength and orientation on these properties is investigated at two temperatures of maghemite nanofluids (25 and 30 °C). The results show that the thermal conductivity enhancement of maghemite nanofluids increases with an increase in the magnetic field strength. The highest thermal conductivity enhancement (39.09%) is attained at the following experimental conditions: (1) particle volume fraction: 0.6%, (2) magnetic field strength: 300 Gauss, (3) temperature of maghemite nanofluid: 30 °C and (4) magnetic field orientation: parallel. The results also show that the kinematic viscosity enhancement of the maghemite nanofluids increases with an increase in the magnetic field strength. Likewise, the highest kinematic viscosity enhancement (31.91%) is attained at the above-mentioned experimental conditions. Based on the results, it can be concluded that both the magnetic field strength and orientation has a significant effect on the thermal conductivity and kinematic viscosity enhancement of maghemite nanofluids.